Interactions of warfarin with COVID-19 vaccine/drugs, monoclonal antibodies, and targeted anticancer agents from real-world data mining - Gao, Yan; Huang, Qingsong; Li, Jun; He, Junsheng; Qian, Fang; Yi, Juanjuan (Frontiers in Pharmacology, 2024)
Objective:This study aims to examine the unresolved drug-drug interactions of warfarin using realworld data.Methods: Electronic medical records from a hospital in Shanghai, China, were used to summarize drug-related problems (DRPs) among inpatients taking warfarin in 2022. Additionally, adverse event data for warfarin from January 2004 to December 2023 were extracted from the U.S. adverse event reporting system to evaluate the bleeding risk associated with the concomitant use of warfarin and COVID-19 Vaccine/drugs, monoclonal antibodies, and targeted anticancer agents.The electronic clinical records yielded 180 cases, of which 130 cases (72.22%) had 276 DRPs identified. DRP5 (n = 172, 64.13%) was identified as the most common issue, comprising 145 drug interactions and 27 adverse drug reactions (ADRs). The analyses of warfarin ADR records (n = 53709) from the database revealed that tocilizumab (adjusted Odds Ratio (aOR): 3.39[95% CI: 1.77-7.03]; P < 0.001), ibrutinib (aOR: 2.53[1.61-4.19]; P < 0.001), and cabozantinib (aOR: 3.34[1.40-9.85]; P = 0.013) significantly increased the risk of warfarin bleeding. In contrast, nirmatrelvir-ritonavir (aOR: 0.32[0.14-0.69]; P = 0.004), adalimumab (aOR: 0.72[0.56-0.93]; P = 0.012), golimumab (aOR: 0.18[0.05-0.50]; P = 0.02), tofacitinib (aOR: 0.51[0.29-0.86]; P = 0.013), and dabrafenib (aOR: 0.17[0.04-0.55]; P = 0.007) significantly reduced the risk of bleeding when combined with warfarin. Remdesivir combined with warfarin was associated with a statistically significant increase in bleeding events (P = 0.047); while the risk was not significant after adjusting for age and sex (aOR: 1.79; P = 0.2). No significant effect was observed with the COVID-19 vaccine (aOR: 0.89; P = 0.8).Drug-drug interactions contribute to the adverse effects of warfarin. This study provides real-world evidence of newly identified drug interactions with warfarin. It reminds clinicians to monitor INR and adjust warfarin doses accordingly when used in combination with these medications.